Evaluation of pulmonary nodules and infection on chest CT with radiation dose equivalent to chest radiography: Prospective intra-individual comparison study to standard dose CT. Issue 2 (February 2016) - Martini, K.; Barth, B.K.; Nguyen-Kim, T.D.L.; Baumueller, S.; Alkadhi, H.; Frauenfelder, T.
Abstract: Purpose: To compare prospectively, in patients undergoing chest computed tomography (CT) for pulmonary-nodules or infection, image-quality and accuracy of standard dose (SD) and reduced dose (RD) CT with tin-filtration. Material and methods: This IRB-approved study included 100 consecutive patients (36 female;median age 56 years) referred for follow-up of pulmonary-nodules ( n  = 43) or suspicion of infection ( n  = 57) undergoing single-energy CT with SD and RD using tin-filtration at 100 kVp (CTDIvol 2.47 mGy and 0.07 mGy, respectively). Images were reconstructed with advanced modeled iterative reconstruction (ADMIRE) at strength 3 and 5. Image-noise was measured. Two independent readers evaluated nodules and pulmonary-infection. SD CT served as reference standard. Results: No significant difference was found in noise between RD with ADMIRE5 and SD with ADMIRE3 (118HU ± 14 vs. 120HU ± 17; p  = 0.08). Sensitivity for detection of atelectasis and interstitial lung changes was higher in images reconstructed with ADMIRE5 (93% and 88%; respectively) than in those reconstructed with ADIMRE3 (77% and 78%; respectively). Sensitivity for detection of consolidations was 90% for ADMIRE3 and 89% for ADMIRE5. Sensitivity for nodule detection was 71% for ADMIRE3 and 81% for ADMIRE5. Specificity for detection of atelectasis and interstitial lung changes was 99% and 96% with ADMIRE5 and 99% and 96% with ADMIRE3. Specificity for detection of consolidations was 99% for ADMIRE3 and 5. Specificity for detection of nodules was 87% for both ADMIRE3 and 5. Conclusion: Chest CT with a radiation dose equivalent to conventional radiography is feasible and allows for detection of pulmonary infection with high sensitivity, whereas the accuracy for detecting nodules is only moderate.